Molecular detection of Anaplasma platys in a naturally-infected cat in Brazil - Lima,M.L.F (2010)
Following the accidental finding of inclusion bodies similar to Anaplasma platys in a stained blood smear from a cat, DNA analysis of the 16S rRNA gene was performed and 100% identity was found with different strains of A. platys. These data confirm that cats are susceptible to parasitism by A. platys.